Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1089/ten.tea.2019.0152
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rat Liver Machine Perfusion System for Normothermic and Subnormothermic Conditions

Abstract: Ex vivo liver machine perfusion (MP) is a promising alternative for preservation of liver grafts from extended criteria donors. Small animal models can be used to evaluate different perfusion conditions. We here describe the development of a miniaturized ex vivo MP system for rat liver grafts, evaluating cell-free and erythrocyte-based perfusion solutions, subnormothermic and normothermic temperatures, and dialysis. A perfusion chamber was designed after a suitable liver position was identified. Normothermic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…compared single and dual vessel NEVLP but were unable to accomplish perfusion periods of longer than 90 minutes without witnessing a severe escalation of arterial perfusion pressure and transaminase levels [ 30 ]. Reasons for that could include the lack of a dialysis circuit and the utilization of a cell free perfusate, as previous findings of our work group show [ 31 , 23 ]. Brüggenwirth et al .…”
Section: Discussionmentioning
confidence: 87%
“…compared single and dual vessel NEVLP but were unable to accomplish perfusion periods of longer than 90 minutes without witnessing a severe escalation of arterial perfusion pressure and transaminase levels [ 30 ]. Reasons for that could include the lack of a dialysis circuit and the utilization of a cell free perfusate, as previous findings of our work group show [ 31 , 23 ]. Brüggenwirth et al .…”
Section: Discussionmentioning
confidence: 87%
“…Both group 1 and group 3 livers had mean ALT levels within transplantable criteria during 6 hours of NMP while group 2 and group 4 livers did not meet ALT transplantable criteria by 6 hours. [25,31] The differences in mean ALT levels between group 2 and 3 livers did not reach statistical signi cance by 6 hours (492 ± 98 vs. 278 ± 91 units/L, p = 0.069) (Fig. 3B).…”
Section: Perfusion Injury Markersmentioning
confidence: 89%
“…Both group 1 and group 3 livers had mean AST levels within transplantable criteria during 6 hours of NMP while group 2 and group 4 livers did not meet AST transplantable criteria by 6 hours. [25,31] Compared to cold UW ush livers with SCS (group 2), RT LR ush livers with SCS (group 3) had lower mean AST levels at 6 hours of NMP (629 ± 121 vs. 351 ± 97 units/L, p = 0.046) (Fig. 3A).…”
Section: Perfusion Injury Markersmentioning
confidence: 96%
“… 6 However, it has been reported that metabolism can be suppressed by reducing the perfusion temperature, and studies have been conducted to investigate the metabolic status of the perfusate in ex vivo perfusion. 11 , 12 Based on these studies, metabolic studies in pigs are of great value because the metabolism of pigs is similar to that of humans. The required components of ex vivo perfusion were examined by comparing perfusion ex vivo with 10% diluted blood and whole blood collected from donors.…”
Section: Discussionmentioning
confidence: 99%